Post-tensioned infills effect on lateral resistance of industrialized building system - Mohammed, Bashar Hassen (2014)
Industrialized building system (IBS) has many advantages compared to the conventional cast in-situ construction. The adoption of IBS is slow, especially in the areas subjected to severe earthquakes. The main objective of this study is to investigate the effect of cyclic lateral load of post-tensioned infilled IBS system. It studies the mechanism of failure of IBS system assemblies to a certain performance loads. The method used in this study is entirely laboratory procedural to obtain the result of lateral displacement due to the effect of the post-tensioning infills and making the beams as integral units to the walls infills. It was learned from the experiment that post-tensioned infills to upper beams of IBS frame improves the rigidity of the IBS system as a whole